2017
DOI: 10.1002/evl3.28
|View full text |Cite
|
Sign up to set email alerts
|

FeminizingWolbachiaendosymbiont disrupts maternal sex chromosome inheritance in a butterfly species

Abstract: Wolbachia is a maternally inherited ubiquitous endosymbiotic bacterium of arthropods that displays a diverse repertoire of host reproductive manipulations. For the first time, we demonstrate that Wolbachia manipulates sex chromosome inheritance in a sexually reproducing insect. Eurema mandarina butterfly females on Tanegashima Island, Japan, are infected with the wFem Wolbachia strain and produce all‐female offspring, while antibiotic treatment results in male offspring. Fluorescence in situ hybridization (FIS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 54 publications
(109 reference statements)
2
28
0
1
Order By: Relevance
“…Our results show that sex chromosome genotype represents yet another case of host nuclear control over symbiont transmission. Wolbachia symbionts were previously found to prevent sex chromosome transmission in Eurema mandarina butterflies [46]. Here we show that sex chromosomes can prevent Wolbachia transmission in A. nasatum , thereby offering a whole new perspective on the molecular interplay between feminizing symbionts and host sex chromosomes.…”
Section: Discussionsupporting
confidence: 51%
“…Our results show that sex chromosome genotype represents yet another case of host nuclear control over symbiont transmission. Wolbachia symbionts were previously found to prevent sex chromosome transmission in Eurema mandarina butterflies [46]. Here we show that sex chromosomes can prevent Wolbachia transmission in A. nasatum , thereby offering a whole new perspective on the molecular interplay between feminizing symbionts and host sex chromosomes.…”
Section: Discussionsupporting
confidence: 51%
“…Males were stored at −30°C until DNA extraction. After allowing females to lay eggs in the laboratory for other experiments [21,24], bursa copulatrixes and Malpighian tubules were dissected out from them and the remains were stored at −30°C until DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…It was recently revealed that, like the majority of lepidopteran insects, C females have the WZ karyotype and C males have the ZZ karyotype. In contrast, CF females have the Z0 karyotype [23,24]. By mating with C males, CF females produce embryos that are all Z0, whose Z chromosomes are paternally derived (i.e., Wolbachia -induced disruption of maternal inheritance of the Z chromosome).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations